Theoretical proposals of graphene-based electronic devices - Araújo, Francisco Ronan Viana (2021)
Graphene has been extensively investigated after its isolation in 2004 by A. K. Geim and K. S. Novoselov. Due to its remarkable electronic and transport properties, it has become a promising candidate to replace silicon in the production of field-effect transistors (heart of the electronics industry). However, turning off the current via gate potentials in graphene-based electronic devices can be a challenge due to Klein tunneling. In recent years, there has been an expressive search for theoretical and experimental proposals capable of modulating the current, avoiding the limitation imposed by Klein tunneling. In this sense, three electronic devices based on graphene nanoribbons were investigated in this Thesis, namely: (i) graphene p-n junction that acts as a Veselago lens, (ii) three-terminal ballistic junction of graphene (graphene Y-junction), and (iii) graphene quantum ring in the presence of a perpendicular magnetic field. Numerical simulations of quantum transport using a tight-binding model were performed in (i) and (ii). In (i), it was demonstrated that the application of an in-plane electric field or a perpendicular magnetic field changes the position of the output focus of the Veselago lens, reducing the conductance between the input and output terminals. In (ii), it was found that a gate potential applied to one of the graphene Y-junction terminals can properly modulate the current between the input terminal and the two output terminals. Finally, in (iii), a numerical approximation using the tight-binding model was compared to an analytical approach using the continuum model in order to show that the persistent current can be tuned through a gate potential applied to one of the graphene quantum ring arms. The electronic devices presented in this Thesis can benefit from the high mobility of charge carriers in graphene and represent viable theoretical proposals for the development of low-power field-effect transistors.